Developement of dynamic online publication review system - Zhang, Chao (2011)
The project is to develop a Dynamic Online Publication System. The system is used by 3 types of users, the editor, the authors and the reviewer. The editor is the system administrator in the meanwhile. The authors and reviewers are supposed to use this system upon invitation from the editor. This system serves as an online platform for each member of the 3 user groups to interact with each other, in order to collect the qualified manuscripts and publish them as a journal or textbook.